2018
DOI: 10.1002/mmce.21658
|View full text |Cite
|
Sign up to set email alerts
|

The design of radio frequency energy harvesting and radio frequency-based wireless power transfer system for battery-less self-sustaining applications

Abstract: In this paper, the RF energy harvesting system and RF-based wireless power transfer system are proposed and designed for battery-less self-sustaining application. For energy harvesting, the designed antenna array improves the received RF power effectively and also can harvest RF energy in multi-frequency bands. For wireless power transfer, the proposed helical antenna realizes the system design in miniaturization. Subsequently, the T shape LC matching network are designed between the antenna and the rectifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The bandwidth of the proposed harvesting cube ranged from 1.85 to 1.93 GHz and from 2 to 2.10 GHz, respectively, covering GSM-1800 and Universal Mobile Telecommunications System (UMTS-2100) with cell networking bands. Zhang et al [30] proposed and designed an RF energy harvesting system and RF-based wireless power transfer system for applications that are self-sustaining and battery-less. An overview of a reported studies of energy harvesting is summarized and demonstrated in Table 1…”
Section: Energy Harvestingmentioning
confidence: 99%
“…The bandwidth of the proposed harvesting cube ranged from 1.85 to 1.93 GHz and from 2 to 2.10 GHz, respectively, covering GSM-1800 and Universal Mobile Telecommunications System (UMTS-2100) with cell networking bands. Zhang et al [30] proposed and designed an RF energy harvesting system and RF-based wireless power transfer system for applications that are self-sustaining and battery-less. An overview of a reported studies of energy harvesting is summarized and demonstrated in Table 1…”
Section: Energy Harvestingmentioning
confidence: 99%
“…In this context, there has been a growing interest of researchers in the development of the WPT systems. In particular, there is an increasing interest in near-field WPTs as they have a broad application area, such as implantable medical devices, 3 consumer electronics, 4 low-power sensors, 5,6 radio-frequency identification, 7,8 wireless body area network, 9 and so forth. In general, there are three distinct techniques to achieve near-field WPT, namely, capacitive, 10 inductive, 11 and magnetic resonance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, radio frequency identification (RFID), with a high data rate from a batteryless tag to a reader, is gaining interest. The lack of a battery is an important advantage for the tag because it avoids replacing or recharging the battery, increases devices durability, and prevents using high cost components 1,2 . The batteryless tags have various applications: they were implanted in animal and human bodies to monitor the temperature, 3‐6 near field communication and wireless power transfer 7,8 .…”
Section: Introductionmentioning
confidence: 99%